Natural Killer T Cells in Various Mouse Models of Hepatitis - Guan, Jun (Biomed Res Int, 2021)
Natural killer T (NKT) cells are a key component of innate immunity. Importantly, a growing body of evidence indicates that NKT cells play an integral role in various acute and chronic liver injuries. NKT cells participate in the progression of an injury through the secretion of cytokines, which promote neutrophil infiltration and enhance Fas ligand (FasL) and granzyme-mediated NKT cytotoxic activity. Therefore, examining the role of NKT cells in hepatic disease is critical for a comprehensive understanding of disease pathogenesis and may provide insight into novel approaches for treatment. For more than a century, mouse models that imitate the physiopathological conditions of human disease have served as a critical tool in biological and medical basic research, including studies of liver disease. Here, we review the role of NKT cells in various mouse models of hepatitis.